A sample of relatively unstudied star clusters in the Large Magellanic Cloud: fundamental parameters determined from Washington photometry - Palma, Tali (2013)
Aims. To enlarge our growing sample of well-studied star clusters in the Large Magellanic Cloud (LMC), we present CCD Washington CT1 photometry to T1 ∼ 23 in the fields of twenty-three mostly unstudied clusters located in the inner disc and outer regions of the LMC. Methods. We estimated cluster radii from star counts. Using the cluster Washington (T1,C − T1) colour–magnitude diagrams, statistically cleaned from field star contamination, we derived cluster ages and metallicities from a comparison with theoretical isochrones of the Padova group. Whenever possible, we also derived ages using δT1 – the magnitude difference between the red giant clump and the main sequence turn off – and estimated metallicities from the standard giant branch procedure. We enlarged our sample by adding clusters with published ages and metallicities determined on a similar scale by applying the same methods. We examined relationships between their positions in the LMC, ages, and metallicities. Results. We find that the two methods for age and metallicity determination agree well with each other. Fourteen clusters are found to be intermediate-age clusters (1−2 Gyr), with [Fe/H] values ranging from −0.4 to −0.7. The remaining nine clusters turn out to be younger than 1 Gyr, with metallicities between 0.0 and −0.4. Conclusions. Our 23 clusters represent an increase of ∼30% in the current total amount number of well-studied LMC clusters using Washington photometry. In agreement with previous studies, we find no evidence for a metallicity gradient. We also find that the younger clusters were formed closer to the LMC centre than the older ones.